Electric power distribution handbook - Short, T. A. (Tom A.) 1966- (Electric power engineering series, 2014)
Of the "big three" components of electrical infrastructure, distribution typically gets the least attention. In fact, a thorough, up-to-date treatment of the subject hasn't been published in years, yet deregulation and technical changes have increased the need for better information. Filling this void, the Electric Power Distribution Handbook delivers comprehensive, cutting-edge coverage of the electrical aspects of power distribution systems. The first few chapters of this pragmatic guidebook focus on equipment-oriented information and applications such as choosing transformer connections, sizing and placing capacitors, and setting regulators. The middle portion discusses reliability and power quality, while the end tackles lightning protection, grounding, and safety.